Flexibilização e intensificação laboral: manifestações da precarização do trabalho e suas consequências para o trabalhador - Lima, Camilla Alves (2012)
The terms flexibilization and work intensification have been addressed, many times, as equivalents to precarization. We see these concepts as distinct and consider that the intensification and flexibilization may be configured as consequences of a generalized process of vulnerability of the work conditions, typical of the last decades. Based on these assumptions, the aim of the present paper is to present flexibilization and intensification, marks of the current labor scenery, as manifestations of the work precarization process. In order to achieve this purpose, we will consider historical reflections on emergence of the phenomena in question, especially from the productive restructuring processes of the 70 ́s. We will start from a brief historical review that allow us understand the current moment and then we will bring antagonistic conceptions of the term flexibilization. Finally, we will present this process as an opportunity to work intensification and the consequent damages to the worker.